Managing employment relations/ Tony Bennett, Virginia Fisher, Richard Saundry. - Bennett, Tony (Anthony); Fisher, Virginia; Saundry, Richard; Gennard, John.; Chartered Institute of Personnel and Development (London Kogan Page Limited, 2020)
Employment relations is concerned with the relationship between employees and their employers and is one of the most important aspects of an HR role. Managing Employment Relations will give students a thorough grounding in the processes, context and practical application of employment relations and give them the knowledge and skills they need for a successful career in HR. Covering everything from the legal aspects of employment relations, essential policies, strategies and the changing social context to conflict resolution, mediation, employee engagement and workplace discipline, Managing Employment Relations is an indispensable guide. With brand new content on gig economy workers, supporting diversity in the workplace, individual and group policies and the need for greater transparency in the employer-employee relationship, this book is a comprehensive guide to the theory and practice of employment relations. Mapped to the CIPD Level 7 module in employment relations and full of case studies and exercises to help students understand the practical application of the core topics, this is an essential textbook for postgraduate HR students and practitioners in an employment relations role. Online resources include a lecturer guide, lecture slides, sample essay questions and additional case studies for students and lecturers as well as annotated weblinks.
Chapter 01. Introduction -- Chapter 02. The concepts and processes of employment relations -- Chapter 03. The context of employment relations -- Chapter 04. Employment relations and the law -- Chapter 05. The global environment -- Chapter 06. Employment relations strategies, policies and change -- Chapter 07. Employee engagement -- Chapter 08. Managing employment relations -- Chapter 09. Employee representation -- Chapter 10. Employee involvement and participation -- Chapter 11. Managing workplace conflict -- Chapter 12. Managing workplace discipline -- Chapter 13. Managing employee grievances -- Chapter 14. Managing redundancy -- Chapter 15. The role of mediation in conflict resolution -- Chapter 16. Conclusion - Thoughts for the future.
"CIPD" -- title page.
Previous edition: published as by John Gennard, Graham Judge, Tony Bennett and Richard Saundry. London: Chartered Institute of Personnel and Development, 2016.
Includes bibliographical references and index.
Keywords: Personnel management; Industrial relations; Industrial relations; Personnel management